RADIOGRAPHIC VERSUS NON-RADIOGRAPHIC AXIAL SPONDYLOARTHRITIS: RESULTS FROM TREASURE DATABASE - Kilic, L.; Ayan, G.; Atagunduz, P.; Akar, S.; Bilge, N. S. Yasar; Dalkilic, E.; Ertenli, A. I. (Bmj Publishing Group, 2023)
[Abstract Not Available]
European Congress of Rheumatology (EULAR) -- MAY 31-JUN 03, 2023 -- Milan, ITALY
Keywords: Real-world evidence; Outcome measures; Registries